Genome-Wide SNP Markers Based on SLAF-Seq Uncover Breeding Traces in Rapeseed (Brassica napus L.) - Zhou, Qinghong; Zhou, Can; Zheng, Wei; Mason, Annaliese S.; Fan, Shuying; Wu, Caijun; Fu, Donghui; Huang, Yingjin (Frontiers in Plant Science, 2017)
SNPs (Single Nucleotide Polymorphisms) are the most abundant and richest form of genomic polymorphism, and hence make highly favorable markers for genetic map construction and genome-wide association studies. In this study, a total of 300 rapeseed accessions (278 representative of Chinese germplasm, plus 22 outgroup accessions of different origins and ecotypes) were collected and sequenced using SLAF-seq (Specific-Locus Amplified Fragment Sequencing) technology, obtaining 660.25M reads with an average sequencing depth of 6.27 × and a mean Q30 of 85.96%. Based on the 238,711 polymorphic SLAF tags a total of 1,197,282 SNPs were discovered, and a subset of 201,817 SNPs with minor allele frequency > 0.05 and integrity > 0.8 were selected. Of these, 30,877 were designated SNP “hotspots”, and 41 SNP-rich genomic regions could be delineated, with 100 genes associated with plant resistance, vernalization response and signal transduction detected in these regions. Subsequent analysis of genetic diversity, linkage disequilibrium and population structure in the 300 accessions was carried out based on the 201,817 SNPs. Nine subpopulations were observed based on the population structure analysis. Hierarchical clustering and principal component analysis divided the 300 varieties roughly in accordance with their ecotype. However, spring-type varieties were intermingled with semi-winter type varieties, indicating frequent hybridization between spring and semi-winter ecotypes in China. In addition, linkage disequilibrium (LD) decay across the whole genome averaged 299 kb when r2=0.1, but the LD decay in the A genome (43 kb) was much shorter than in the C genome (1455 kb), supporting the targeted introgression of the A genome from progenitor species B. rapa into Chinese rapeseed. This study also lays the foundation for genetic analysis of important agronomic traits using this rapeseed population.